Uncanny x-force (2010), volume 2 ebook - Remender, Rick (Uncanny X-Force (2010), 2012)
Collects Uncanny X-Force #5-7 & 5.1. They come in waves, an army of time displaced Deathlok troopers made from Earth's greatest warriors: Captain America, Spider-Man, Elektra, Cyclops, Venom, The Thing, Bullseye--all soldiers in the army of Deathlok. All operating under one directive: Fantomex must die! Can X-Force stop Earth's Mightiest Deathloks? Author: Rick Remender. Illustrator: Esad Ribic, Rafael Albuquerque. © 2020 Marvel Characters, Inc. All rights reserved. All characters featured in this issue and the distinctive names and likenesses thereof, and all related indicia are trademarks of Marvel Characters, Inc. No similarity between any of the names, characters, persons, and/or institutions in this magazine with those of any living or dead person or institution is intended, and any such similarity which may exist is purely coincidental. www.marvel.com.com